Myocyte-Specific Upregulation of ACE2 in Cardiovascular Disease: Implications for SARS-CoV-2–Mediated Myocarditis. Issue 7 (18th August 2020) - Tucker, Nathan R.; Chaffin, Mark; Bedi, Kenneth C.; Papangeli, Irinna; Akkad, Amer-Denis; Arduini, Alessandro; Hayat, Sikander; Eraslan, Gökcen; Muus, Christoph; Bhattacharyya, Roby P.; Stegmann, Christian M.; Margulies, Kenneth B.; et al.
Abstract : Supplemental Digital Content is available in the text.